BERAT BADAN BAYI USIA 0-6 BULAN YANG DIBERI ASI TANPA SUSU FORMULA DENGAN BERAT BADAN BAYI YANG DIBERI SUSU FORMULA - NUNUK NURHAYATI NUNUK NURHAYATI (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Breastfeeding is common in all cultures and is always done because the baby's survival depends on breast milk (ASI). Baby milk can be given to babies if breast milk production is reduced or because of the mother's willingness to give baby milk. baby feeding must be by the dose and should not be excessive because it can cause overweight in the baby. Based on a survey in early March 2022 at the Akbar Medika Clinic, Mojokerto on 10 babies, it was found that 6 babies were exclusively breastfed and 4 babies were given baby milk. Based on this, it is necessary to do further research. The purpose of this study was to determine the weight of infants aged 0-6 months who were breastfed without baby milk and the weight of infants fed baby milk. The research instrument was a questionnaire and an observational research design using analytic methods. The sample in this study were infants aged 0-6 months who visited the Akbar Medika Clinic in March - May 2022 as many as 34 babies. The results showed that infants who were breastfed without baby milk experienced a weight gain of 76.2% according to the standard (16 infants) and the weight of infants fed baby milk without breast milk experienced a non-standard weight gain of 69.2% (9 Baby ). The results of the test with Chi-Square (χ2) = 6.839 P: 009 then there is a relationship between the weight of infants aged 0-6 months who are breastfed without baby milk with those who are given baby milk. Mothers are expected to always give breast milk to children aged 0-6 months to increase the baby's weight and to increase the baby's immunity so that they don't get sick easily. And for health workers, especially midwives, to always provide explanations, information, and education to pregnant women or mothers who have given birth to babies so that babies are given breast milk because breast milk is the best food for babies.